Academic visit of semester three Bachelor of Plantation and Management students - Chan, Margaret Kit Yok (UiTM Sarawak, 2016)
With the financial subsidies from the Tabung Amanah Pembangunan Akademik Pe/a/ar (TAPA), a group of thirty-five Semester Three students from the Faculty of Plantation and Agrotechnology participated in a study tour from 10th to 13th December 2015. The tour was led by Associate Professor Dr. Margaret Chan and Mr Amirul Bin Othman. The study tour was a fulfillment of three cources: Agricultural Product Marketing (AGR513), Crop Diseases (AGRS14) and Plantation Weed Management (AGR524) which aim to broaden students' horizons and give students an opportunity to relate thier lectures to the real world situations.